Has the Great Recession Raised U.S. Structural Unemployment? - Estevao, Marcello (IMF Working Papers; Working Paper, 2011)
The recent crisis has had differential effects across U.S. states and industries causing a wide geographic dispersion in skill mismatches and housing market performance. We document these facts and, using data from the 50 states plus D.C from 1991 to 2008, we present econometric evidence that supports that changes in state-level unemployment rates are linked to skill mismatches and housing market performance even after controlling for cyclical effects. This result suggests some causality going from mismatches and housing conditions to unemployment rates. The numerical estimates imply that the structural unemployment rate in 2010 was about 1 3/4 percentage points higher than before the onset of the housing market meltdown at end-2006. Reversing this increase may require targeted active labor market policies and measures to expedite the adjustment in housing markets, as our results suggest weak housing market conditions interact negatively with skill mismatches to produce higher unemployment rates in the United States.